Exploring the Landscape of Digital Entrepreneurship among Disabled People: A Bibliometric Analysis - Rahmawati Rahmawati; Rochmat Aldy Purnomo; Ari Kuncara Widagdo; Noor Ismawati Jaafar; Farzana Parveen Tajudeen; Endang Dwi Amperawati; Sri Hartoko; Agus Dwianto (Qubahan Academic Journal)
This study delves into the landscape of digital entrepreneurship among people with disabilities through a bibliometric and cartographic analysis. Four key research questions guide the investigation: 1) What pattern have publications about digital entrepreneurship of people with disability shown throughout the years?, (2) Which writers and nations have made the most significant contributions to the literature on digital entrepreneurship of people with disability?, (3) Which journals publish the most articles about the digital entrepreneurship of people with disabilities?, and (4) What are the most popular keywords found in digital entrepreneurship of people with disability documents. The research unveils trends, prominent contributors, leading publication outlets, and prevalent themes in digital entrepreneurship among individuals with disabilities. Furthermore, employing cartographic analyses with VOSviewer, the study maps out the interconnectedness and collaboration networks among authors, nations, and keywords, offering insights into the global research landscape in this critical area. By shedding light on the existing body of literature and research dynamics, this study contributes to a deeper understanding of digital entrepreneurship within the disability context. It informs future research directions and policy initiatives to foster inclusivity and innovation in entrepreneurship